If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = -3 + -16 Reorder the terms: 2 + 6x = -3 + -16 Combine like terms: -3 + -16 = -19 2 + 6x = -19 Solving 2 + 6x = -19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6x = -19 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = -19 + -2 6x = -19 + -2 Combine like terms: -19 + -2 = -21 6x = -21 Divide each side by '6'. x = -3.5 Simplifying x = -3.5
| (x-2)(x+7)=x-2 | | 2+16q=50 | | -3(2c)+4(5c)+11=81 | | 3=t+11.5-t | | 5/28=h/36 | | x+3.5=9.0 | | A=JP | | 22.47/0.7 | | -3.2=t+(0.2) | | 9x+6-7(x+1)=6x+2 | | 4/5+65/7-97/9 | | 8x^3y^4-6x^2y^3= | | 2/35=h/65 | | 1/7(6t-9)=t+9/14 | | 9x-2(4x+5)=2x-(4-x)-12 | | 5(z+4)+6z=97 | | 2/x+1=8/12 | | 12.92/3.4 | | 5/5x+6/5x=33 | | -43-(13)=x/2 | | 14x=736 | | a=(20-2x) | | x^2+14= | | x^2+14x | | 7p=50+5p | | m/3=9/4 | | -5(4y-6)-y=-3(y-4) | | 1/2(8x+10) | | 0.50(9.0+-1y)+0.20y=3.45 | | 4/3y+9+y-3/2y-6=-2 | | 10=5x+3x-8 | | W^2-8w+24=0 |